An Analysis of Expressive Illocutionary Acts Found In Sherlock Holmes: A Game of Shadows - Desak Kadek Melani Sukma Prajadewi; Ida Ayu Mela Tustiawati (BULLET : Jurnal Multidisiplin Ilmu, 2022)
Language is an important aspect of communication that is used to interact, speak, and express feelings. The aspects of speech acts that are usually used in communication are expressive speech acts. This study aims to identify and analyze the illocutionary acts of expressive categories by examining the dialogue in the movie. The results of the analysis show that the movie Sherlock Holmes: A Game of Shadows uses several expressive types, namely; Thank, Compliment, Greet and Welcome, Apologize, Complaint, Congratulate and Boast. In addition to examining these categories, the purpose of this research is to study the types of expressive Illocutionary acts that are useful in communication. The meaning of expressive illocutionary acts in this film is thanking, giving praise and pride, expressing greeting and welcoming, apologizing, giving complaints, congratulating, and boasting.